(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
Growth response of Spirulina platensis in papaya skin extract media and their antimicrobial activity were studied. Five different concentrations e.g. 10gm/L, 8gm/L, 6 gm/L, 4 gm/L and 2gm/L of Papaya (Carica papaya) skin extract media and BD1 (control) medium were used in this study. After 8 days of cultivation, the optical density (0.33) was recorded in BD1 medium and among the five different concentrations of papaya skin extract media the maximum was found (0.31) in 6gm/L. Antimicrobial activity of Spirulina platensis grown in three media namely Zarrouk, BD1 media and media made from papaya skin extract was also studied. Only freeze dried Spirulina platensis powder extract showed inhibitory effect against bacteria and no antifungal activity was observed. DOI: http://dx.doi.org/10.3329/bjsir.v47i2.11445 Bangladesh J. Sci. Ind. Res. 47(2), 147-152, 2012